Settlement of Traffic Offences: A Shift in the Presumption of Innocence and the Impact on Legal Justice - Beny Harkat; Nandang Sambas; Chepi Ali Firman Zakaria (Journal La Sociale, 2024)
Traffic offences are a serious issue in Indonesia, creating complex challenges for the justice system and social costs. Although Law No. 22/2009 has defined the rules, the high number of accidents and offences indicates the ineffectiveness of law enforcement. This study aims to investigate the impact of traffic offences on legal justice, the effectiveness of sanctions, and the shifting presumption of innocence in Indonesia. The research methodology included both quantitative and qualitative approaches, involving analyses of accident data and interviews with authorities. The results showed a high number of offences, a lack of effectiveness of Law No. 22 of 2009, and the phenomenon of "peace in place." The implementation of ETLE cameras became an alternative, despite internet access constraints. Perma No. 12/2016 changed the judicial process, moving from a presumption of innocence to a presumption of guilt. This shift provides uniform sanctions without considering individual circumstances. The limitation of violators' rights in ticket hearings violates the principle of justice. The implementation of e-ticket technology shows advantages, but the dependence on the internet and the potential for misuse are obstacles. The shift to the presumption of innocence in the Perma raises doubts about the fairness of the justice system. Improving fairness requires a re-evaluation of the application of sanctions, technological improvements, and a deeper understanding of the rights of offenders. These recommendations are expected to improve the justice system related to traffic offences in Indonesia.